2020
DOI: 10.3390/pr8010120
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Low-Temperature Polyvinyl Chloride Carbonization by Catalytic CuAl Layered Double Hydroxide

Abstract: A good way to make carbon materials was presented in low-temperature polyvinyl chloride (PVC) carbonization by catalysis. The process of low-temperature PVC carbonization by CuAl-layered double hydroxide (CuAl-LDH) was investigated by thermogravimetric analysis (TGA) and tubular furnace. The results show that CuAl-LDH accounting for 5% of PVC mass enabled acceleration of the dehydrochlorination in PVC as soon as possible and maximized the yield of the PVC carbonized product. The vacuum with 0.08 MPa, 20 °C/min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…In addition, the greater residue mass at the end of pyrolysis suggests that CuAl-LDH can effectively promote the cross-linking reaction between molecules to produce more stable carbon rather than volatile hydrocarbons. Pang et al 136 also found the catalytic effect of CuAl-LDH on the low-temperature carbonization of PVC. It has been documented that polybenzimidazole can increase the temperature of the first part of PVC pyrolysis to improve its thermal stability.…”
Section: Feedstock Recyclingmentioning
confidence: 95%
“…In addition, the greater residue mass at the end of pyrolysis suggests that CuAl-LDH can effectively promote the cross-linking reaction between molecules to produce more stable carbon rather than volatile hydrocarbons. Pang et al 136 also found the catalytic effect of CuAl-LDH on the low-temperature carbonization of PVC. It has been documented that polybenzimidazole can increase the temperature of the first part of PVC pyrolysis to improve its thermal stability.…”
Section: Feedstock Recyclingmentioning
confidence: 95%
“…The Special Issue showcases ten full-length original research articles [13][14][15][16][17][18][19][20][21][22], one short communication [23], and one review article [24] covering different aspects of various processes for bioenergy and resource recovery from biowaste. Specifically, the accepted manuscripts covered a range of essential topics in the areas of anaerobic digestion, microbial fermentation, and thermochemical conversion targeting various value-added resources, including biogas, syngas, bio-oil, and organic acids ( Figure 1).…”
Section: Statistics Of the Special Issuementioning
confidence: 99%